2021
DOI: 10.3390/ani11010191
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Epidemiology of Leptospirosis: A Review of Leptospira Isolations from “Unconventional” Hosts

Abstract: Leptospirosis is a re-emerging worldwide zoonotic disease. Even though the primary serological test for diagnosis and surveying is the microscopic agglutination test (MAT), isolation remains the gold-standard test to detect Leptospira infections. The leptospirosis transmission is linked to maintenance and accidental hosts. In the epidemiology of Leptospira some serovar are strictly related to specific maintenance hosts; however, in recent years, the bacterium was isolated from an even wider spectrum of species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 121 publications
0
30
0
4
Order By: Relevance
“…Leptospirosis is a cosmopolitan zoonosis caused by bacteria belonging to the genus Leptospira, which is well known for infecting humans and a wide variety of domesticated and wild vertebrates [1]. Leptospira species have been described also in several 'unconventional' hosts [2] such as reptiles [3], amphibians [4], and cetaceans [5,6], as well as from many other different orders, suggesting that most microbial diversity in hosts is largely unknown. Humans can become infected by direct exposure to infected animals and their products (urines or body fluids) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Leptospirosis is a cosmopolitan zoonosis caused by bacteria belonging to the genus Leptospira, which is well known for infecting humans and a wide variety of domesticated and wild vertebrates [1]. Leptospira species have been described also in several 'unconventional' hosts [2] such as reptiles [3], amphibians [4], and cetaceans [5,6], as well as from many other different orders, suggesting that most microbial diversity in hosts is largely unknown. Humans can become infected by direct exposure to infected animals and their products (urines or body fluids) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wildlife diseases occur in numerous forms in a wide range of species and populations around the globe. Leptospirosis is a zoonosis of global importance, affecting many species of wild and domestic animals, as well as humans [ 1 , 3 ]. Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Infections with Leptospira spp. can affect not only people in exposed professions (i.e., veterinarians, trappers, abattoir workers, farm workers, hunters, animal shelter workers and scientists and technicians involved with animals in laboratories or in the field) but also people who work with marine mammals, fishmen, researchers, wildlife rehabilitators, animal trainers and zoological park workers [ 3 ]. A study conducted in Austria [ 29 ] reported that hunters in particular are exposed to zoonotic agents, including leptospires, probably through the direct contact of abraded skin or mucous membranes with the tissues, blood or urine of infected animals [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria resides in the kidneys of these animals, and they commonly do not show clinical signs of the disease. The presence of Leptospira in wild animals including mammals (mainly rodentia), birds, reptiles, and amphibians, have been thoroughly reviewed by Vieira et al (2018) and Cilia et al (2021), where many unconventional hosts were identified in North and Latin-American countries. Although wildlife has a real role in the Leptospira transmission cycles, information is still scarce for many regions of the world (Vieira et al, 2018).…”
Section: Biotic Factorsmentioning
confidence: 99%
“…Leptospirosis, caused by spirochetal bacteria of the Leptospira genus, is considered the most widely distributed zoonotic disease on the planet (Samsudin et al, 2018). Leptospira has been isolated in many vertebrate taxa, including mammals, birds, amphibians, reptiles, and fish (Viera et al, 2018;Cilia et al, 2021), and has shown genetic heterogeneity. Leptospirosis represents a disease associated with poverty and low sanitation environments, both in rural and urban communities, as well as in livestock production areas, where close interaction with animals could favor the leptospirosis spread.…”
Section: Introductionmentioning
confidence: 99%